Destructed and Endangered Habitats in the Syrian Coast, and Ways of Rehabilitation - Ibrahim, Amir; Hussein , Chirine; AlShawi , Firas (Latakia University Journal -Biological Sciences Series, 2023)
This research was carried out along the Syrian coast, where the areas threatened with inundation because of the expected sea level rise were studied, and seven sites measuring ~45.7 km are expected to be affected. Among the habitats destructed by marine erosion, 3 areas measuring ~8.45 km were observed. The coastal rivers (32 outlets and 6 estuaries) were also studied in terms of threats and pollutants. The areas of eutrophication were studied, and four sites were detected (Qandil River estuary, Al-Azhari sewage discharge outlet, northern of Al-Roos River, and Al-Rumaila River outlet). A number of sand and gravel removal sites were also observed. Likewise, the sites affected by fragmentation along the Syrian coast were looked for, whether on the coast as a result of waterways or road passages, or in coastal marine waters as a result of pollutants or warm water discharges. A number of field projects were proposed for rehabilitating damaged places: some are at legislation level and strategies development, and some are at integrated planning level or civil-construction projects. The research is the first of its kind to be carried out on the Syrian coast.